Letters of a lifetime - Moodie, Susanna, 1803-1885 (CEL - Canadian Publishers Collection., 1993)
First published in 1985, this volume of letters follows Susanna Moodie from her Suffolk girlhood and her experience as an aspiring young writer in London, through her emigration to Upper Canada and five decades of Canadian life. The letters provide a sense of Moodie's literary accomplishments before her emigration, the long, uncertain struggle to develop her career as a writer in the colony, and the brief but intense period of literary activity during which her books were published in Britain and the U.S.